Occurrence analysis of alpha-mangostin from different organs of Garcinia mangostana L. - Ahmad Izuren Shah, Nurin Syamimi; Abu Bakar, Mohd Rushdi; Bakhtiar, M. Taher; Danial, Wan Hazman; Adam, Fatmawati; Abd Rahim, Syarifah (Taylor & Francis, 2025)
Alpha-mangostin (AM) is a naturally occurring xanthone with remarkable pharmacological properties, including anti-inflammatory, anti-bacterial, and antioxidant effects. The compound is commonly extracted from the pericarps of Garcinia mangostana L. fruits, but its seasonal availability is limited. Investigating the potential of using various organs of the tree for AM extraction can help mitigate limitations imposed by the seasonal availability of fruits. This study employs the Soxhlet extraction method and gravitational column chromatography for the preparation of AM from various plant organs. The purity of the compound in the extract was quantitatively determined using high-performance liquid chromatography analysis. The stem barks demonstrated the highest yield at 1.3%, with a concentration of 324.593 μg/mL and a purity of 95.215% for AM. The finding is expected to assist in uncovering alternative sources of AM and contribute to sustainable utilisation of the tree, as various plant organs could be employed in AM extraction.